One-side oscillation strategic approach - Beausoleil, Ricardo (2013)
This paper reports an approach developed to find a good quality solution for a generalized assignment problem with application to the Dimensional Cutting Problem. The objective at the Cutting Problemis to divide different pools of pieces of the same dimension among different items of available material all having two dimensions, the width and length. The solution is found keeping the largest number of pieces in a single material. Some initial numerical experiences found for the algorithm optimal and suboptimal solutions orinstances of more than 500 pieces at a very low computational cost.